Precision medicine: the emerging approach to the chronic pain patient. (August 2013) - Oren, Ohad; Ablin, Jacob
Chronic pain is a major public health issue. Its management mandates a multidisciplinary clinical assessment. Over the past decades, the individual variation in response to analgesic medication has been shown to be tightly mediated by the pharmacogenetic profile. Better understanding of the molecular basis of pain complemented by gradual unraveling of genotype–phenotype associations hold important implications for clinical utility and safety in the field of pain management. However, as the pain community embraces the accumulation of genomic data, it is worthwhile analyzing the caveats of a pure gene-derived approach and consider the many environmental factors that affect the highly complex phenomenon of pain.